Mitophagy in neuronal health and disease: from mechanisms to neurodegeneration - Bishal Basak; Julia F. Riley; Neha M. Nataraj; Erika L.F. Holzbaur (Journal of Clinical Investigation, 2026)
Regulation of mitochondrial health is critical for maintaining cellular homeostasis in the nervous system. Damaged mitochondria can have detrimental effects on neuronal health and are thought to be key contributors to the progression of neurodegenerative disorders including Parkinson’s disease and amyotrophic lateral sclerosis. To mitigate this damage, multiple quality control mechanisms have evolved to eliminate aged or damaged mitochondria. One such quality control process is autophagy, a process that involves turnover of mitochondria at presynaptic sites and the axon terminal under basal conditions. This highly conserved mechanism sequesters mitochondria from the cytosol within autophagosomes followed by degradation upon fusion with a lysosome. Acute mitochondrial damage activates a selective form of autophagy called mitophagy that involves receptor-mediated engulfment and degradation of the damaged organelle. Multiple mechanisms have been shown to drive efficient mitophagy in neurons and glia, including PTEN induced kinase 1 (PINK1)/Parkin–dependent mitophagy and receptor-mediated mitophagy. Genetic, pathological, and experimental evidence all implicate defects in the removal of damaged mitochondria in the onset or progression of neurodegenerative disease. Both the initiation of PINK1/Parkin–dependent mitophagy and deficits in the removal of damaged mitochondria are linked to activation of neuroinflammatory pathways, including NF-κB and cyclic GMP-AMP synthase–stimulator of interferon genes (cGAS-STING) signaling. In this Review, we discuss the molecular pathways governing mitophagy in neurons and glial cells and how deficits in these pathways may lead to neurodegeneration. We also highlight emerging therapeutic strategies aimed at restoring mitophagy to preserve neuronal homeostasis and function.